Tauromachies et temporalités : un système de transformations entre sport et art du spectacle - Frédéric Saumade (Temporalités)
Focusing on the formal resemblances and differences between the rules of the « system of sports » and those governing bullfights, one sees that both are generally characterized by the rationalistic concept of the relation to time. Calling upon a structuralist methodology based on a comparative ethnographic survey (from South-West Europe to North America), the author highlights the relativity of arena games. He shows that the principles of temporality as they are observed through the different kinds of spectacles, from the Spanish corrida to the American rodeo, with or without killing the animal, may be reduced to a quadrant, that is to say a four-part structure of correlations and oppositions. Such a structural formula confers its coherence to a mode of performance that is paradoxical because constantly swinging between sports, circus, tragedy, comedy and the control of life-and-death cycles through the confrontation of humans and their animals.